Human dehydrogenase/reductase SDR family member 11 (DHRS11) and aldo-keto reductase 1C isoforms in comparison: Substrate and reaction specificity in the reduction of 11-keto-C19-steroids. Issue 199 (May 2020) - Endo, Satoshi; Morikawa, Yoshifumi; Kudo, Yudai; Suenami, Koichi; Matsunaga, Toshiyuki; Ikari, Akira; Hara, Akira
Graphical abstract: Highlights: Kinetic reactivity to 11-ketosteroids is compared among DHRS11 and AKR1C isoforms. DHRS11 reduces 17-keto groups of the steroids with lower K m values than AKR1C3. AKR1C4 reduces 11-ketodihydrotestosterone (11KDHT) more efficiently than AKR1C2. Both 3α- and 3β-metabolites are detected in GC/MS analysis of the 11KDHT reduction. Val200 is a critical determinant for exhibiting the strict 17β-HSD activity of DHRS11. Abstract: Recent studies have shown that an adrenal steroid 11β-hydroxy-4-androstene-3, 17-dione serves as the precursor to androgens, 11-ketotestosterone and 11-ketodihydrotestosterone (11KDHT). The biosynthetic pathways include the reduction of 3- and 17-keto groups of the androgen precursors 11-keto-C19 -steroids, which has been reported to be mediated by three human enzymes; aldo-keto reductase (AKR)1C2, AKR1C3 and 17β-hydroxysteroid dehydrogenase (HSD) type-3. To explore the contribution of the enzymes in the reductive metabolism, we kinetically compared the substrate specificity for 11-keto-C19 -steroids among purified recombinant preparations of four AKRs (1C1, 1C2, 1C3 and 1C4) and DHRS11, which shows 17β-HSD activity. Although AKR1C1 did not reduce the 11-keto-C19 -steroids, AKR1C3 and DHRS11 reduced 17-keto groups of 11-keto-4-androstene-3, 17-dione, 11-keto-5α-androstane-3, 17-dione (11K-Adione) and 11-ketoandrosterone with K m values of 5–28 μM. The 3-keto groups of 11KDHT and 11K-Adione were reduced by AKR1C4 ( K m 1 μM) more efficiently than by AKR1C2 ( K m 5 and 8 μM, respectively). GC/MS analysis of the products showed that DHRS11 acts as 17β-HSD, and that AKR1C2 and AKR1C4 are predominantly 3α-HSDs, but formed a minor 3β-metabolite from 11KDHT. Since DHRS11 was thus newly identified as 11-keto-C19 -steroid reductase, we also investigated its substrate-binding mode by molecular docking and site-directed mutagenesis of Thr163 and Val200, and found the following structural features: 1). There is a space that accommodates the 11-keto group of the 11-keto-C19 -steroids in the substrate-binding site. 2) Val200 is a critical determinant for exhibiting the strict 17β-HSD activity of the enzyme, because the Val200Leu mutation resulted in both significant impairment of the 17β-HSD activity and emergence of 3β-HSD activity towards 5α-androstanes including 11KDHT.